Processing and characterization of nanosized oxide based hybrid materials - He, Chunyun (2014)
Nowadays, nanotechnology had been widely used in the industry of pharmacy, chemistry and materials. Nanomaterial has attracted great interest of scientists due to its great properties like the large surface area to volume ratio, unique optical property and size dependent property. In the area of material science, the Nano oxide is very important considering its application in catalyst, lubricant and surfactant.